Economic-accounting aspects of solving the problem of carbon emission - Milojević Ivan M.; Mihajlović Milan B.; Vladisavljević Vladan D. (Војно дело, 2015)
Due to economic differentiation in the world negative effects occurred at a global level. Non-global approach to the problem in rich countries caused the pollution to become a global problem because of their policies of transferring 'dirty' technologies into 'third world' countries. This is why it is necessary to introduce the solution of the global problem in economic dimension by introducing oxygen as the fifth main productive element, the others being soil, labour, capital and knowledge. In connection to this, growing consumption and feedback in production cause growing oxygen consumption through their visible forms.